Adaptação brasileira de um programa interdisciplinar de reabilitação em dor baseado em ACT (Terapia de Aceitação e Compromisso) - Siqueira, Jose Luiz Dias [UNIFESP] (2018)
Interdisciplinary programs have been identified for more than three decades as viable and effective resources in the treatment of different types of chronic pain. Most of them are conceptually based on the fundamentals of Behavioral Therapy or Cognitive Behavioral Therapy (CBT). Although CBT is consolidated as one of the most important resources of treatment for chronic pain, there is still room for improvement in some aspects. Objective: The present study sought to investigate the efficacy of adapting an Acceptance and Commitment Therapy (ACT) based interdisciplinary pain program to the Brazilian reality. Methods: Forty-three patients with chronic pain participated in this study. The program was composed of 10 weekly sessions of 4 hours each. All the professionals involved received training in the fundamentals of Acceptance and Commitment Therapy (ACT) previously. Results: The analyzes indicate significant differences in the physical tests and the questionnaires regarding acceptance of pain, anxiety and functional aspects. The results are in agreement with other clinical trials in other countries. Conclusion: This study highlights the potential of the program for the treatment of people with chronic pain and the need for further studies to deepen this initial analysis.